Effect of Ambient Noise on Pure Tone Hearing Screening Test Conducted in Indian Rural Locations - Ajish K. Abraham; Chandni Jain; L, Yashaswini (Journal of All India Institute of Speech and Hearing)
Pure tone hearing screening test is the most widely used method for detecting hearing impairment. To avoid false positive results, the test needs to be conducted in a quiet environment with ambient noise levels lesser than the maximum permissible noise levels speci ed by ANSI. Such an environment is not available in the rural areas of India. As per census 2011, 49% of the persons with hearing impairment in India live in rural areas, which emphasize the need to conduct hearing screening in rural locations. No attempts have been made yet to document the ambient noise levels in these rural locations and to nd out how these noise levels in uence the test results. The present study was an e ort to measure the ambient noise levels in three of such locations and to nd the e ect of these noise levels on the outcome of the hearing screening test conducted on 15 participants at each of these locations. The selected locations were found to have average ambient noise levels of 58.3, 60.1 and 64.8 dBSPL, which were higher than the ambient noise levels reported in the previous studies. Results showed very low speci city at 500Hz test frequency at all the three locations when the pass criterion was 25 dBHL while it was 80% when the pass criterion was 30 dBHL. 100% speci city was observed at all other test frequencies, at all the three locations. Outcome of the study will help to precisely organize hearing screening programs in Indian rural areas.